Effects of artificial ripening of banana (Musa spp) using calcium carbide on acceptability and nutritional quality - Nura, Abdullahi; Dandago, Munir Abba; Wali , Naja atu Rabiu (Journal of Postharvest Technology, 2018)
Freshly harvested bunches of green matured banana were collected from a private garden in Dawakin kudu Local Government while Calcium carbide was purchased from Na’ibawa fruit Market all in Kano State. Different levels (0, 5, 10, 15, 20 and 25 g/kg) of CaC2 coded A, B, C, D, E and F were used in a two stage ripening method adopted to emulate the process used by local banana retailers in Kano State, Nigeria. During the first stage, bunches of banana and CaC2 were enclosed in an airtight HDPE chamber for 48 hours at 34±8°C while in the second stage the HDPE was replaced with jute bag and water sprinkled regularly to maintain low temperature and minimize water loss. This stage was maintained at 32±8°C for 22 hours. Parameters evaluated were proximate composition, vitamin C, titratable acidity and pH. Sensory parameters evaluated were appearance, sweetness, aroma, firmness, mouth feel and acceptability. Percentage moisture, ash and lipid were found to be increasing with increase in CaC2 concentration. Protein, fibre and carbohydrates contents were found to be decreasing with increase in CaC2 concentration. Vitamin C, titratable acidity and pH contents were also found to be decreasing with increase in CaC2 concentration. Samples with 20 and 25g CaC2/kg fruit were found to have the best sensory characteristics but results in higher moisture which may significantly affects the shelf life of the fruits. Higher ash contents recorded in samples E and F was a reflection of high concentration of CaC2 used in their ripening.